Corpos, Violências E Algumas Obstinações Feministas - Guazzelli Bernardes, Anita; de Campos Maciel, Josemar; Marques, Camilla Fernandes; Maria de Fátima Guareschi, Neuza (Revista Polis e Psique, 2024)
Apresentação do Dossiê